Peripheral DNA damage in active pulmonary tuberculosis - SELEK, ŞAHABETTİN; Selek, Sahbettin; KOÇYİĞİT, ABDÜRRAHİM; ASLAN, Mehmet; Horoz, Mehmet; Celik, Hakim; Cosar, Niyet; Gunak, Faruk; Kocyigit, ABDÜRRAHİM (My University, 2012)
In pulmonary tuberculosis patients, little is known about peripheral DNA damage, although increased oxidative stress is a well documented entity. Therefore, we aimed to investigate DNA damage along with oxidative status parameters in pulmonary tuberculosis patients. Twenty-seven pulmonary tuberculosis patients and 26 controls were included. DNA damage was assessed by comet assay. Total oxidant and antioxidant status, and oxidative stress index were determined. DNA damage, total oxidant status and oxidative stress index were higher in pulmonary tuberculosis patients than controls (all P < 0.05), while total antioxidant status was lower (P < 0.05). DNA damage was correlated with total oxidant and antioxidant status, and oxidative stress index (r = 0.69, P < 0.05; r = 0.48, P < 0.05, r = -0.47, P < 0.05; respectively) in pulmonary tuberculosis patients. Oxidative stress and DNA damage are increased in pulmonary tuberculosis patients. Increased oxidative stress associated DNA damage may be one of the pathogenetic mechanisms involved in the disorders suggested to be associated with pulmonary tuberculosis. (C) 2011 Wiley Periodicals, Inc. Environ Toxicol, 2012.